Dental Health Knowledge Increased as a Result of Dental Health Education on Elderly Denture Care in Surabaya, Indonesia - Nur Rahmania, Primanda; Dahlan, Agus; Kamadjaja, Michael Josef Kridanto; Prirastika, Pramesti; Pramesti, Rheyna Anissa; Adam, Syafira Salsabila (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: Losing teeth as a result of tooth extraction is a concern since it can affect speech impairment, temporomandibular junction (TMJ) dysfunction, masticatory dysfunction, and psychological disorders, specifically aesthetics. A fixed denture or a removable denture must be made to replace missing teeth in order to preserve the quality of life of the patient. Purpose: to describe the improvement in oral and dental health knowledge that resulted from dental health education about how to care for dentures in the nursing home. Methods: The data collection was done by two surveyors. The sample size for this study was 50 individuals over the age of 50. Under the direction of Jagir Health Centre, Pelangi and Lestari nursing home to educate the elderly about the instruction on how to take care of dentures. For the pre- and post-tests, the participants were required to complete a questionnaire in order to assess how their knowledge of oral and dental health had changed. Results: The presentation on oral and dental health education was mostly grasped by the participants. In comparison to the pre-test rate (58%), the post-test percentage (98%) was higher. Conclusion: This study showed that enhancement of elderly awareness of their oral and dental health condition through dental health education was a successful approach.